2003
DOI: 10.1074/jbc.m302651200
|View full text |Cite
|
Sign up to set email alerts
|

RNA-structural Mimicry in Escherichia coli Ribosomal Protein L4-dependent Regulation of the S10 Operon

Abstract: Ribosomal protein L4 regulates the 11-gene S10 operon in Escherichia coli by acting, in concert with transcription factor NusA, to cause premature transcription termination at a Rho-independent termination site in the leader sequence. This process presumably involves L4 interaction with the leader mRNA. Here, we report direct, specific, and independent binding of ribosomal protein L4 to the S10 mRNA leader in vitro. Most of the binding energy is contributed by a small hairpin structure within the leader region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…First, the S2 binding to the 59-UTR promoted by S1 may provoke a rearrangement of the mRNA leader structure inhibitory for translation-initiation complex formation; in this case, translational repression of the rpsB mRNA may exert a polar effect on the tsf expression via breaking the transcription-translation coupling within rpsB. Alternatively, the S2-mRNA complex itself or in concert with other factors may directly stimulate preliminary transcription termination, as in the case of the L4-mediated repression of the S10 operon (Zengel and Lindahl 1994;Stelzl et al 2003). Future experiments (mainly in vitro) will shed light upon the fine mechanism underlying the S2-mediated negative control of the rpsB-tsf expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the S2 binding to the 59-UTR promoted by S1 may provoke a rearrangement of the mRNA leader structure inhibitory for translation-initiation complex formation; in this case, translational repression of the rpsB mRNA may exert a polar effect on the tsf expression via breaking the transcription-translation coupling within rpsB. Alternatively, the S2-mRNA complex itself or in concert with other factors may directly stimulate preliminary transcription termination, as in the case of the L4-mediated repression of the S10 operon (Zengel and Lindahl 1994;Stelzl et al 2003). Future experiments (mainly in vitro) will shed light upon the fine mechanism underlying the S2-mediated negative control of the rpsB-tsf expression.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the primary r-proteins acting as autogenous regulators (e.g., S7, S8, S15, L1, L4, L20) recognize similar targets on free rRNA and on mRNA of its cognate operon (Zengel and Lindahl 1994;Guillier et al 2002Guillier et al , 2005Stelzl et al 2003;Mathy et al 2004), indicating that the autogenous control is based on molecular mimicry as was originally proposed by Nomura (Nomura et al 1980). A detailed analysis of the refined crystal structure of the T. thermophilus 30S subunit at 3.05Å resolution revealed that S2 is located on the back of 30S and spans the head-body hinge region by forming contacts with 16S rRNA helices H26 in the body and H35-H37 in the head of the subunit (Brodersen et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Hairpin HD is required for efficient L4 control of transcription in E. coli (29) and is essential for binding of L4 to the S10 leader in vitro (20), but deletion of HD has little effect on translation (29). We deleted hairpin HD from the V. cholerae leader and observed significantly reduced inhibition of expression of the fusion protein (Fig.…”
Section: Fig 1 (A)mentioning
confidence: 99%
“…This hairpin seems to be required only for the L25-mediated control but not for translation efficiency, since its deletions increased the translation yield, simultaneously decreasing autogenous repression. At first glance, a set of base parings within HII does not resemble the L25 target on 5S rRNA, the loop E, so that at present it is hard to suggest (or to rule out) that binding of L25 to its mRNA mimics its interaction with 5S rRNA, following the principle of "molecular mimicry" earlier proposed for a number of r-protein operons (Nomura et al 1980;Stelzl et al 2003;Mathy et al 2004;Guillier et al 2005;Fu et al 2014).…”
Section: Autogenous Control Of the Rply Mrnamentioning
confidence: 99%